The disturbance of fluvial gravel substrates by signal crayfish (Pacifastacus leniusculus) and the implications for coarse sediment transport in gravel-bed rivers - Matthew F. Johnson (2010)
Signal crayfish are an internationally widespread invasive species that can have important detrimental ecological impacts. This thesis aims to determine whether signal crayfish have the potential to also impact the physical environment in rivers. A series of experiments were undertaken in purpose-built still-water aquaria using a laser scanner to obtain Digital Elevation Models (DEMs) of narrowly-graded gravel surfaces before and after exposure to crayfish. The difference between DEMs was used to quantify volumetric changes in surface topography due to crayfish activity. Two distinct types of topographic change were identified. The first was the construction of pits and mounds which resulted in an increase in surface roughness and grain exposure. The second was the rearrangement of surface material caused by crayfish brushing past grains when walking and foraging, reorientating grains and altering friction angles. A series of 80 flume runs were undertaken to quantify alterations made by crayfish to water-worked, as well as loose, gravel substrates at low velocity flows. Crayfish significantly altered the structure of water-worked substrates, reversing the imbrication of surface grains to a more random arrangement. Surfaces were entrained at a relatively high velocity flow subsequent to crayfish activity in order to directly link topographic and structural alterations to substrate stability. Nearly twice as many grains were mobilised from surfaces which had been disturbed by crayfish in comparison to control surfaces that were not exposed to crayfish. A field investigation aimed to determine the potential significance of the geomorphic impact of crayfish in rivers. Signal crayfish were tracked through a 20 m reach of a small, lowland alluvial river for 150 days using a Passive Integrated Transponder (PIT) system. Crayfish were active throughout the channel, although their activity became limited as water temperature dropped and flow stage increased. Substrate was not an important determinant of crayfish activity at this scale. Instead, crayfish tended to be found along the inner bank of a meander bend where there was a substantial cover of macrophytes. Consequently, signal crayfish were active for extended periods on substrates of a similar size to those that they could disturb in flume experiments. These results suggest that signal crayfish could have important geomorphic effects in rivers, disturbing bed structures and increasing the mobility of coarse material. This may have important implications for both the management of some rivers and benthic organisms that reside on the river bed.